Hair disorders in autoimmune diseases - Rodríguez Tamez, Giselle; Herz Ruelas, Maira Elizabeth; Gómez Flores, Minerva; Ocampo Candiani, Jorge; Chávez Álvarez, Sonia (Karger, 2023)
Alopecia is a common feature in several autoimmune diseases. With a wide spectrum of clinical presentations, it may manifest with a scarring or non-scarring nature, in a diffuse, patchy, or localized pattern. We as dermatologists have the opportunity of assessing patients with hair loss who may have an underlying undiagnosed autoimmune disorder. This review aimed to describe the main clinical, trichoscopic, and histopathological features of hair disorders associated with autoimmune diseases.